10.1016/s0029-7437(05)70735-7 (CrossRef Listing of Deleted DOIs, 2000)
Aim To examine the dimensions and meanings of the work environment of Primary Health Care nurses in relation to organizational conditions and professional practice. Design Sequential explanatory mixed-methods study. Methods This study was conducted with Primary Health Care nurses in Manaus, Brazil. The quantitative phase included 243 participants using a validated work environment scale, analysed descriptively and compared across health districts. The qualitative phase involved 16 interviews analysed through thematic analysis. The phases were integrated using joint displays and meta-inferences to connect, compare and interpret the findings. Results Work motivation was classified as healthy, particularly regarding meaning, recognition and autonomy, whereas safety and strategic management fell within the attention range, without differences across the districts. The qualitative findings confirmed and expanded these results and, for motivation, reframed them: motivation rested on the meaning nurses attribute to care rather than on favourable conditions, compensating for weaknesses in safety and management, the most fragile dimension. Conclusion The work environment is sustained from within, through professional commitment, whereas the structures that should protect and organize the work remain fragile, especially in a territorially complex, resource-constrained Amazonian setting. Implications for the profession The findings support continuous, institutionalized strategies for worker protection, violence prevention, psychological support and participatory management. Impact This study shows that professional engagement coexists with organizational challenges, informing policy and workforce interventions. Reporting method STROBE and COREQ guidelines. No patient or public involvement No patient or public involvement.